Regulatory Standards in Orphan Medicinal Product Designation in the EU - Tsigkos, Stelios; Mariz, Segundo; Sheean, Maria Elzbieta; Larsson, Kristina; Magrelli, Armando; Stoyanova-Beninska, Violeta (Frontiers in Medicine, 2021)
Twenty years of orphan regulation in Europe have now elapsed, with almost 2400 orphan designated medicinal products and more than 190 orphan products authorised in the EU. Alongside the evolution in understanding of rare diseases, considerable regulatory knowledge has also been accumulated regarding the level of evidence that would support inclusion of products into the framework. This article reviews publications and regulatory documents pertaining to orphan medicinal product designation in the EU and discusses the general expectations in submitted applications as reflected in the current regulatory practice. Important elements to recommend granting a European orphan designation are the key considerations of orphan condition, medical plausibility, seriousness and prevalence, while significant benefit is also assessed when there are authorised medicinal products for the sought indication. This review attempts to clarify the specific concepts currently used in that regard and discusses how the available data can be used to justify the criteria for designation. Moving away from theoretical expectations or assumptions, it stresses that the applications have to be complemented with nosological and epidemiological justifications pertaining to the proposed condition, as well as relevant data in specific non-clinical in vivo models or in affected patients to support inclusion into the orphan scheme.